Orthodontic Treatment Characteristics and Outcomes in an Educational Setting - T. Al-Jewair; V. Ryan; S. Warunek (International Journal of Dentistry)
Background. To assess and correlate orthodontic treatment characteristics and outcomes in an educational setting. Methods. A total of 287 patients were included. Independent chart reviews were conducted to gather demographic and pretreatment diagnostic information. Posttreatment digital records were graded with the ABO C-R Eval and the CCA methods. Pearson correlation coefficients were calculated to determine associations between variables. Results. Of the 287 patients, 122 (42.5%) were male and 165 (57.5%) were female. The total average treatment time was 33.87 ± 10.28 months, with a range from 11 to 75 months. The mean ABO C-R Eval score was 29.10 ± 8.59 points. The parameters with the highest scores were buccolingual inclination and occlusal contacts. The mean CCA score was 3.36 ± 2.05 points. The highest scores were recorded for dental esthetics and management of the periodontium. Higher ABO DI scores were weakly correlated with longer treatment times (r = 0.258; p<0.001). ABO C-R Eval scores showed a weakly significant association with treatment duration (r = 0.162; p=0.006), while CCA scores were moderately associated with treatment duration (r = 0.451; p<0.001). Conclusions. As treatment duration increased, the total ABO C-R Eval and CCA scores tended to increase; thus, quality of treatment outcomes decreased. A significant positive correlation was also found with the ABO DI score and treatment duration.